Semiotic Analysis of Kekal Song by Nadin Amizah: Michael Rifaterre Study - Zalwa Aliya; Izzah (Raja Zulkarnain Education Foundation, 2025)
This analysis contains a semiotic analysis of Nadin Amizah's song